THE EFFECT of BALANCED NUTRITION EDUCATION on NUTRITION FULFILLMENT BEHAVIOR in an EFFORT TO PREVENT STUNTING in PRECONCEPTION WOMEN - Hidayati, Tutik; Hanifah, Iis (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Nutrition during preconception is the main factor that affects the condition of women of childbearing age during pregnancy and the well-being of the baby. Nutritional status during preconception is one of the determinants of the quality of human life, especially for mothers and babies, with the fulfillment of balanced nutrition. In 2020, the risk of KEK in Indonesia was 9.7% in pregnant women (Ministry of Health, 2021). In 2022, the number of pregnant women experiencing KEK was 5.6%. In Probolinggo Regency in 2021, 12.7% of pregnant women had KEK. Providing nutritional education is one effort to convey nutritional knowledge to preconception women. This study aimed to analyze the Effect of Balanced Nutrition Education on Nutritional Fulfillment Behavior in efforts to prevent stunting in Preconception Women. The research design used was cross-sectional. The population in this study were all preconception women in Gading Village, Probolinggo, totaling 67 people. The sampling technique used was simple random sampling. The sample in this study was some women in Gading Village, Probolinggo, totaling 46 people. The analysis used is the Wilcoxon test statistical test using SPSS. The results of the study obtained the results of the analysis test using the Wilcoxon test showed a sig value of 0.000. Preconception nutritional preparation for prospective mothers is very necessary in preventing stunting.